KARAKTERISTIK KEJADIAN TB PARU PADA ORANG DEWASA DENGAN RIWAYAT VAKSINASI BCG - RYAN NOERFITRA; ANITA SURYA (JURNAL ILMIAH KOHESI, 2023)
According to the World Health Organization (2015) stated that pulmonary tuberculosis has now become a global threat, because almost a third of the world's population has been infected. As many as 95% of cases of pulmonary tuberculosis and 98% of deaths due to pulmonary tuberculosis in the world, occur in developing countries. In an epidemiological perspective, which sees the incidence of disease as a result of the interaction between the three components of the host (host), the cause (agent), and the environment (environment) can be a risk factor for the occurrence of the disease. Prevention by immunization or vaccination is an action that causes a person to have a better body resistance, so that they are able to defend themselves against diseases or germs from outside. Vaccination against tuberculosis is the Bacillus Calmetta-Guerin (BCG) vaccination, which is mandatory in 64 countries and recommended in several others. Objective: To determine the characteristics of the incidence of pulmonary TB in adults with a history of BCG vaccination. descriptive with cross sectional approach, sampling method using retrospective technique. Research data obtained from primary data using questionnaires and physical examination instruments. The results showed the prevalence of BCG Immunization Status was 77.8%. Characteristics of pulmonary TB patients showed that it was more common at the age of 36-45, male (77.8%), high school education (70.4%), underweight nutritional status (55.6%) and smoking (66.7%). The high prevalence of BCG immunization does not necessarily prevent pulmonary TB itself. Depending on the risk factors that each individual has.